Release kinetics of rosemary (Rosmarinus officinalis) polyphenols from polyvinyl alcohol (PVA) electrospun nanofibers in several food simulants. (December 2018) - Estevez-Areco, Santiago; Guz, Lucas; Candal, Roberto; Goyanes, Silvia
Graphical abstract: Highlights: Rosemary extract was successfully incorporated within PVA electrospun mats. Active mats retained most of the rosemary polyphenols present in the extract. Higher amount of polyphenols was burst released in hydrophobic simulant. Polymer chain relaxation is the main release mechanism in hydrophilic simulant. Both polymer chain relaxation and Fick diffusion contributes in acid simulant. Abstract: Polyvinyl alcohol (PVA) electrospun mats with antioxidant activity (PVA/Ros) were obtained by incorporating rosemary extract (RE) into the electrospinning precursor solution. RE compounds interact with PVA, favoring the retention of polyphenols (88 ± 2%), and improving its thermal stability. The components extracted from PVA/Ros mat were the same as those of the RE. PVA/Ros mats showed a polyphenol content of (15.4 ± 0.5) mg gallic acid equivalent/g of mat (mg GAE/g) and achieved an antioxidant activity of (120 ± 8) μmoles Trolox equivalent/g of mat (μmol TE/g), as measured by Folin-Ciocalteu method and DPPH assay. The release rate of rosemary polyphenols to several food simulants was measured and kinetic data was adjusted by Fick's diffusion law, Power Law, and Weibull model. The resulting parameters suggested that polymer chain relaxation is the leading mechanism in hydrophilic simulant, while an anomalous release occurred in acid medium. A burst release was observed in lipophilic food simulant, limiting its effectiveness over time. This work shows the potential application of PVA/Ros mats as active food packaging, particularly for hydrophilic and acid food products.